Developing an Interactive E-Booklet Based on Multimedia Learning Theory to Improve Learning Outcomes on Biodiversity - Yachsifa Muna; Aida Fitriani Sitompul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Students frequently struggle with biodiversity concepts due to abstract materials and conventional, static text-based learning. This study aimed to develop, assess the feasibility and practicality, and evaluate the effectiveness of an interactive e-booklet based on multimedia learning theory to enhance student learning outcomes. Utilizing a 4D Research and Development (R&D) model, a sample of 50 tenth-grade students was selected via cluster sampling and divided equally into experimental and control classes at SMA Islam Al Ulum Terpadu Medan. Data gathered through validation sheets, practicality questionnaires, and pretest-posttest cognitive instruments were analyzed using Normalized Gain (N-Gain) and Mann–Whitney U tests. Material experts validated the product as Very Feasible with a 100% consistency score. Practicality metrics increased significantly from Feasible (67.50%) to Very Feasible (86.25%) for teachers, and consistently remained Very Feasible for students in small-group (78.13%) and large-group (88.30%) trials. Crucially, the experimental group achieved a higher posttest average of 93.00 and a medium N-Gain of 0.42, significantly outperforming the control group's posttest average of 80.00 and low N-Gain of 0.25 (Z-count > Z-table). This research contributes an innovative digital solution that actively mitigates cognitive overload, facilitates autonomous learning, and provides teachers with a proven pedagogical tool to optimize students’ conceptual mastery in biology education.